Using Social Media Marketing to Create Brand Awareness, Brand Image, and Brand Loyalty on Tourism Sector in Indonesia - Santi Rimadias; Nesta Alvionita; Adinda Putri Amelia (Bina Nusantara University, 2021)
The research aimed to examine factors that formed brand awareness and brand image of the tourism sector in Indonesia by using social media marketing on TikTok platform. The research applied a quantitative method to do a survey of 220 respondents who were users of the TikTok application. Data collection was carried out from April to May 2021, and processed by using Structural Equation Model Partial Least Square (SEM PLS). Convenience sampling was used in the research. The results show that entertainment, electronic word of mouth, and interaction positively affect consumer brand engagement. Trendiness and customization do not affect consumer brand engagement. Furthermore, it is found that consumer brand engagement positively affects brand loyalty, brand awareness, and brand image. The implication of the research is a reference for managers and policymakers in formulating strategies to improve the tourism sector in Indonesia using the model Social Media Marketing on TikTok.